2018
DOI: 10.1155/2018/5276528
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Contrast Cryolipolysis for Subcutaneous-Fat Reduction

Abstract: Cryolipolysis is the noninvasive treatment of localized fat through cold-induced panniculitis. The purpose of the present study was to evaluate the safety and efficacy of contrast cryolipolysis for subcutaneous-fat reduction. Contrast cryolipolysis mixes the principles of conventional cryolipolysis and periods of heating in accordance with the contrast lipocryolysis process. Twenty-one subjects aged 34 ± 9 years were treated with contrast cryolipolysis in the regions of abdomen and flanks through the Polarys® … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
0
18
1
Order By: Relevance
“…The current study results were in contrast with other studies, which concluded that Cryolipolysis is safe and effective in reducing the fat layer and improving body contouring but without any significant effect on lipid profile and liver enzymes [14,15,48]. However, the other studies' findings depended on either an application of one session of Cryolipolysis [15,48], or repeated applications [14] without any control of the diet, so the significant effect of Cryolipolysis group might also enhanced by the effect of low caloric diet. Also the current study was in contrast to another study, which approved that another reshaping modality increased the blood lipid level [49].…”
Section: Discussioncontrasting
confidence: 99%
“…The current study results were in contrast with other studies, which concluded that Cryolipolysis is safe and effective in reducing the fat layer and improving body contouring but without any significant effect on lipid profile and liver enzymes [14,15,48]. However, the other studies' findings depended on either an application of one session of Cryolipolysis [15,48], or repeated applications [14] without any control of the diet, so the significant effect of Cryolipolysis group might also enhanced by the effect of low caloric diet. Also the current study was in contrast to another study, which approved that another reshaping modality increased the blood lipid level [49].…”
Section: Discussioncontrasting
confidence: 99%
“…23,24 The circumferences of the extremities were reduced significantly up to 2 cm, and the fat layer by almost one-third. Savacini et al observed similar results when cryolipolysis was used for esthetic flank contouring, 25 including a significant subcutaneous fat layer reduction, confirmed in further studies of the submental region (of 2.0 mm), the inner thighs (of 2.8 mm), the lateral thighs (of 2.6 mm), and the saddlebacks. 12,16,[25][26][27] Unfortunately, there is no comparative data available measuring the subcutaneous fat layer reduction after flap contouring by liposuction or partial excision.…”
Section: Discussionmentioning
confidence: 58%
“…On the contrary, studies concluded that cryolipolysis does not lead to significant changes in this outcome. However, these studies assessed the application of cryolipolysis alone, without any dietary control, which helps to reinforce results above 32–34 …”
Section: Discussionmentioning
confidence: 99%
“…However, these studies assessed the application of cryolipolysis alone, without any dietary control, which helps to reinforce results above. [32][33][34] Author, year…”
Section: Discussionmentioning
confidence: 99%